ANALISIS SUFISTIK KONSEP SUKSMA SEJATI DALAM AJARAN PAGUYUBAN NGESTI TUNGGAL, PANGESTU - Kolis, Nur (ULUL ALBAB Jurnal Studi Islam, 2018)
Pangestu as one of the Javanese spiritual streams has unique characteristics of thought. The concept of the Suksma Sejati as the basic teachings of Pangestu mentioned in Serat Sasangka Jati has in common with the concept of NÃ»r Muá¸¥ammad in tasawuf. The similarity lies in the concept of God, nature, and man, all of which expressed in relation to each other. The concept of the Suksma Sejati and NÃ»r Muá¸¥ammad have concluded that the nature and its content are the locus for the manifestation of God. While the perfect human is the perfect manifestation of him. In addition, Pangestu also states that the Suksma Sejati is the same as Christ. However, in Serat Sasangka Jati there is no conclusion that the Suksma Sejati is the Lord Christ to worship. This study shows that Pangestu has an understanding in consistent with tasawuf's thinking. In Pangestu comprehension, the Suksma Sejati is â€œa part of God,â€ but according to NÃ»r Muá¸¥ammad, the Suksma Sejati is the creation of God as a conductor between servant and God. Although its position is the same as Christ, but he remains a servant who is not worthy of worship.